Analysis of the Factors of Word of Mouth, Consumer Experience, and Consumer Satisfaction Influencing Generation Z's Decision in Choosing a Cellular Provider - Felix Tanoto; Faisal Akbar; Stacey Tanori (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
Generation Z, as digital natives, heavily relies on the internet and tends to choose cellular providers based on network quality, speed, and user experience. Although XL Axiata offers competitive package prices, various complaints regarding signal stability, internet speed, and customer service have led to a decrease in interest from Generation Z. Additionally, the negative influence of word of mouth on social media, unsatisfactory consumer experiences, and low customer satisfaction have contributed to users switching to other providers, such as Telkomsel, which is perceived as more stable. This indicates that service quality and consumer satisfaction are key factors in determining Generation Z's purchasing decisions regarding cellular providers. This study was conducted at Universitas Prima Indonesia using a quantitative causal approach to analyze the impact of word of mouth, consumer experience, and consumer satisfaction on purchasing decisions. A sample of 96 respondents was determined using the Lemeshow formula with accidental sampling technique. The data used consisted of primary and secondary data, which were analyzed using multiple linear regression. Based on the research findings, it can be concluded that word of mouth, consumer experience, and consumer satisfaction each have an impact on Generation Z's decision-making in choosing a cellular provider, and simultaneously, these three variables also significantly influence purchasing decisions.